علاقة المرجعية الدينية بأدوار مؤسسات العمل الدعوي - بن بخمة، رمضان; شامخ، ياسين (University Of Eloued جامعة الوادي, 2024)
تنطلق مشكلة هذا البحث من جدلية مفهوم المرجعية الدينية وارتباطه بدور مؤسسات العمل الدعوي، حيث حفل العالم الإسلامي بمجموعة من المرجعيات الدينية المختلفة بحسب اختلاف وتنوع مذاهبها وأسسها ومبادئها وامتداداتها البيئية والجغرافية، ومن هذا المنطلق نسعى من خلال هذا البحث إلى محاولة تفكيك العلاقة بين مسألة المرجعية الدينية ودور مؤسسات العمل الدعوي؛ وذلك ببيان وتوضيح هذه المسألة وأهميتها وتفسير علاقتها بهذا النوع من المؤسسات وتأثيراتها السلبية والإيجابية، كما نروم من هذا البحث ونهدف إلى تسليط الضوء على أدوار بعض مؤسسات العمل الدعوي البارزة والمتميزة من حيث رصد بعض أنشطتها المختلفة ونفوذها، مع قياس أثر نفوذ المرجعيات الدينية المرتبطة بها ومدى إسهامها في توجيه وتأطير العمل الدعوي، دون أن نغفل الإشارة إلى رؤية هذا النوع من المؤسسات في التخطيط الااستراتيجي للدعوة إلى الله تعالى وتبليغ رسالته إلى العالمين مع إظهار جمال هذا الدين للناس من خلال عمل هذه المؤسسات الدعوية. Abstract: The issue addressed in thisresearch stems from the complex concept of religiousauthority and itsconnection to the roles of da'wah (Islamicmissionarywork) institutions. The Islamic world isrepletewithvariousreligiousauthoritiesthatdifferaccording to their diverse schools of thought, foundations, principles, and environmental and geographical extensions. This researchaims to explore the relationshipbetweenreligiousauthority and the roles of da'wah institutions by clarifying and explainingthis issue, its importance, and interpretingitsrelationship to these institutions alongwithits positive and negative impacts. Additionally, thisresearchaims to highlight the roles of someprominent and distinguishedda'wah institutions by examiningsome of theirdifferentactivities and their influence. It alsomeasures the impact of the religiousauthoritiesassociatedwiththem and their contribution to guiding and framingda'wah efforts. Moreover, itconsiders the strategic planning vision of these institutions in calling to Allah Almighty and conveyingHis message to the world, showcasing the beauty of this religion through the work of theseda'wah institutions.
مداخلة
Keywords: المرجعية الدينية; المؤسسات الدعوية; العمل الدعوي; ReligiousAuthority; Da'wah Institutions; Da'wahWork